2015
DOI: 10.1177/1391561415598462
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dumping Initiations in Indian Manufacturing Industries

Abstract: Anti-dumping as a new protectionist trade policy has evolved as the popular strategy choice for the trading nations. Since the Uruguay Round of World Trade Organization (WTO) (1994), India has been a prominent user of it. This article attempts to explore the possible factors that might have triggered off 90 per cent cases of anti-dumping by five major Indian manufacturing industries over the period 1997-2011. We construct a balanced panel combining data on anti-dumping initiations from the 'Global Antidumping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moore & Zanardi (2009), investigating whether anti-dumping investigations are being used by countries for escape clauses, has concluded that the safety valve argument is not supported and that anti-dumping measures serve to hamper trade liberalization. Zhou & Cuyvers (2009), Zeng (2011), Choi & Kim (2014), Bagchi et al (2015) and Li (2018), similarly macroeconomic variables were effective in anti-dumping investigations, Egger & Nelson (2011) has concluded that the antidumping investigations affected the world trade volume and world welfare. In the literature, it is found that anti-dumping investigations are carried out by retaliation between countries (Moore & Zanardi, 2001: 601-619).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore & Zanardi (2009), investigating whether anti-dumping investigations are being used by countries for escape clauses, has concluded that the safety valve argument is not supported and that anti-dumping measures serve to hamper trade liberalization. Zhou & Cuyvers (2009), Zeng (2011), Choi & Kim (2014), Bagchi et al (2015) and Li (2018), similarly macroeconomic variables were effective in anti-dumping investigations, Egger & Nelson (2011) has concluded that the antidumping investigations affected the world trade volume and world welfare. In the literature, it is found that anti-dumping investigations are carried out by retaliation between countries (Moore & Zanardi, 2001: 601-619).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, the first 17 countries using these instruments and the years 1995 (WTO foundation year) -2016 (date of study) were taken into consideration as a sample according to the WTO database. As a matter of fact, when the studies in the literature are examined, it is considered that the sample time interval (22 years) is sufficient (Knetter & Prusa, 2003;Aggarwal, 2004;Feinberg, 2005;Jallab et al, 2009;Zhou & Cuyvers, 2009;Choi & Kim, 2014;Bagchi et al, 2015). In Table 2, the status and source of variables used in the analysis have been seen.…”
Section: Data Setmentioning
confidence: 99%